2019
DOI: 10.1142/s0219691318500625
|View full text |Cite
|
Sign up to set email alerts
|

The approximations of a function belonging Hölder class Hα[0,1) by second kind Chebyshev wavelet method and applications in solutions of differential equation

Abstract: In this paper, two new estimates [Formula: see text] and [Formula: see text] of a function [Formula: see text] belonging to [Formula: see text] are obtained by Chebyshev wavelet method. These estimators are new, sharper and best possible in Wavelet Analysis. Using this method, the solutions of four differential equations are obtained. These solutions are approximately the same as exact solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We note that the first derivative in (27) depends on U m−1 ðxÞ, i.e., Chebyshev polynomials of the second kind. More specifically, it can be written as a Chebyshev wavelet of the second kind (see [20]). The computation of the derivatives ( 26) is more complicated for p > 1.…”
Section: Differentiability Of Lmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the first derivative in (27) depends on U m−1 ðxÞ, i.e., Chebyshev polynomials of the second kind. More specifically, it can be written as a Chebyshev wavelet of the second kind (see [20]). The computation of the derivatives ( 26) is more complicated for p > 1.…”
Section: Differentiability Of Lmentioning
confidence: 99%
“…Current literature showed that these methods depends on the different operational matrices in the sense of [17][18][19]. Moreover, Chebyshev wavelets provided sharp estimates of functions in Hölder spaces of order α [20].…”
Section: Introductionmentioning
confidence: 99%